Community Service Learning: Perspectives from Adult Education - Pierre Walter (Adult Education Research Conference, 2010)
This paper positions Community Service Learning (CSL) within traditions of adult education, examines related work on international CSL, transformative learning and social justice in higher education, and briefly considers a CSL initiative at a major research university. It concludes with suggestions for further research on CSL in adult education.